The chloroplast genome elucidates the origin of mulberry in Central Asia - Wang, Caihui; Yang, Yutian; Yang, Lu; Ling, Xue; Ma, Zhikun; Zou, Tongqian; Ma, Jian; Zhang, Ming (Frontiers in Plant Science, 2025)
The mulberry (Morus spp.), an economically important crop along the ancient Silk Road, is widely distributed in Central Asia, yet its origins and dispersal history in the region remain unclear. Chloroplast genomes are extensively used for species identification, evolutionary analyses, and phylogenetics. We resequenced and de novo assembled 25 chloroplast genomes from Samarkand, Uzbekistan. Our results reveal that they predominantly comprise two species: white mulberry (Morus alba), originating from East Asia, particularly China; and black mulberry (Morus nigra), native to the Caucasus and Western Asia. Strong genetic links to both eastern and western source populations indicate that bidirectional Silk Road exchanges shaped the region’s mulberry population. These findings provide new insights into the geographic distribution and dispersal history of mulberries. This study enhances our understanding of the ecological and historical dynamics that shaped the spread of economically significant plants.